PENELITIAN EVALUATIF SEBAGAI SALAH SATU MODEL PENELITIAN DALAM BIDANG PENDIDIKAN (Suatu Kajian Konseptual) - Sri Kantun (Economic Education, University of Jember, 2016)
Evaluation research is basically a part of appliedresearch. The important part in an evaluation is the existence of anobjective or expected state, and then these objectives assessed by an evaluation. Evaluation activities are designed to generate data on value, service, or the value of educational phenomena. Theevaluation will be carried out properly if the program included aclear objective, so as to define the results expected to be achievedthrough the conceptual framework methodology on the researchevaluation. There are several models of evaluation that can beselected by the researchers to evaluate the programms, which areCIPP, UCLA, Brinkerhoff and Stake evaluation modelKey Words: Evaluation Research, Education